2017
DOI: 10.1038/cgt.2017.30
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-140-5p inhibits invasion and angiogenesis through targeting VEGF-A in breast cancer

Abstract: MicroRNAs (miRNAs) have been proven to be involved in cell metastasis and angiogenesis by interaction with the target mRNAs. Evidence has been confirmed that miR-140-5p is a tumor suppressor in human cancers such as breast cancer. However, the potential molecular mechanism of miR-140-5p in breast cancer invasion and angiogenesis is still poorly understood. According to our study, we reported that miR-140-5p inhibited the tumor invasion and angiogenesis of breast cancer cells both in vitro and in vivo by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 45 publications
10
93
0
Order By: Relevance
“…One previous study has reported that miR-128 regulates glucose metabolism and cell proliferation in triple-negative BC (25). Lu et al (26) indicated that miR-140-5p was significantly downregulated in BC, and that it may suppress invasion and angiogenesis by targeting vascular endothelial growth factor A. miR-190 has been demonstrated to inhibit BC metastasis by regulating transforming growth factor-β-induced epithelial-mesenchymal transition (27). However, the underlying mechanism by which miR-3677 modulates BC carcinogenesis remains obscure.…”
Section: Expression Levels Of Mir-3677 and Tle3 Exhibit An Inverse Comentioning
confidence: 99%
“…One previous study has reported that miR-128 regulates glucose metabolism and cell proliferation in triple-negative BC (25). Lu et al (26) indicated that miR-140-5p was significantly downregulated in BC, and that it may suppress invasion and angiogenesis by targeting vascular endothelial growth factor A. miR-190 has been demonstrated to inhibit BC metastasis by regulating transforming growth factor-β-induced epithelial-mesenchymal transition (27). However, the underlying mechanism by which miR-3677 modulates BC carcinogenesis remains obscure.…”
Section: Expression Levels Of Mir-3677 and Tle3 Exhibit An Inverse Comentioning
confidence: 99%
“…The reason why miR‐140‐5p was selected as a studying point in the present research was owe to the similar MREs it providing for both MALAT1 and HDAC4. As a member of miRNAs family, miR‐140‐5p is widely reported as a key regulator in many malignant tumors like non‐small‐cell lung cancer, gastric cancer, breast cancer, hypopharyngeal carcinoma and so on . Fang Z reported that miR‐140‐5p suppressed gastric cancer's proliferation, migration, and invasion ability by targeting regulation of YES proto‐oncogene 1(YES1) .…”
Section: Discussionmentioning
confidence: 99%
“…As a member of miRNAs family, miR-140-5p is widely reported as a key regulator in many malignant tumors like non-small-cell lung cancer, gastric cancer, breast cancer, hypopharyngeal carcinoma and so on. [48][49][50][51] Fang Z reported that miR-140-5p suppressed gastric cancer's proliferation, migration, and invasion ability by targeting regulation of YES proto-oncogene 1(YES1). 48 In the present study, we illustrated that miR-140-5p was one of the "bridges" between MALAT1 and HDAC4.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐452 inhibits the migration and invasion of BC cells by directly targeting RAB11A . MiR‐140‐5p inhibits angiogenesis and invasion by targeting VEGF‐A in BC . Hence, miRNAs and target genes could comprise an intricate network and play critical roles in BC metastasis.…”
Section: Introductionmentioning
confidence: 99%